Radio frequency coaxial resonant cavity for compressed natural gas ignition - Mariun, Norman; Khan, Nasrullah; Ahmed Nissirat, Liyth; Aris, Ishak (2011)

(untitled)
The present invention discloses an apparatus that utilizes a radio frequency (FR) coaxial resonant cavity to produce large volume of plasma that is sufficient to ignite lean and ultra lean mixtures for internal comprises of a microwave source for providing microwave signal power, a waveguide-to-coaxial transition for converting the radiated microwave signal to electrical means and a coaxial cable for transmitting the signal to the antenna of resonant cavity that resonates at a specified frequency and generating a plasma.